Pseudomonas aeruginosa Biofilm Growth Inhibition on Medical Plastic Materials by Immobilized Esterases and Acylase. Issue 13 (15th July 2014) - Kisch, Johannes Martin; Utpatel, Christian; Hilterhaus, Lutz; Streit, Wolfgang R.; Liese, Andreas
Abstract Biofilms are matrix‐encapsulated cell aggregates that cause problems in technical and health‐related areas; for example, 65 % of all human infections are biofilm associated. This is mainly due to their ameliorated resistance against antimicrobials and immune systems. Pseudomonas aeruginosa, a biofilm‐forming organism, is commonly responsible for nosocomial infections. Biofilm development is partly mediated by signal molecules, such as acyl‐homoserine lactones (AHLs) in Gram‐negative bacteria. We applied horse liver esterase, porcine kidney acylase, and porcine liver esterase; these can hydrolyze AHLs, thereby inhibiting biofilm formation. As biofilm infections are often related to foreign material introduced into the human body, we immobilized the enzymes on medical plastic materials. Biofilm formation was quantified by Crystal Violet staining and confocal laser scanning microscopy, revealing up to 97 % (on silicone), 54 % (on polyvinyl chloride), and 77 % (on polyurethane) reduced biomass after 68 h growth.